Dependency And Directionality - Dikken, Marcel Den (United Kingdom: Cambridge University Press, 2018)
This book is a must-read for syntacticians, develops an integrated understanding of structure building, movement and locality embedded in a syntactic theory that constructs trees from the top down, presenting an explicit counterweight to the bottom-up derivations pervading the Chomskian mainstream.
Includes Bibliographical reference and index.
Keywords: Deep Structure, Language and Languages-Syntax